Employment diversification of farm households and structural change in the rural economy of the New Member States - Jana Fritzsch; Judith Möllers; Gertrud Buchenrieder (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
Changes in the rural labour market, especially the increase of rural non-farm employment are recognised as one dimension of structural change. Labour allocation decisions are driven by economic incentives such as wage differentials, but also non-economic motives may play a decisive role. This paper summarises theoretical insights and presents an integrated conceptual framework reflecting the drivers of employment shifts. Methodologically, the conceptual framework is implemented in fuzzy logic to analyse the household potential to diversify its income activities. The empirical analysis draws on a survey of 1,077 farm households in rural Bulgaria, Hungary, Poland, Romania, and Slovenia. [...] This report is structured as follows: Chapter 2 presents a review of theory, an integrated theoretical framework as well as an overview of current trends of employment diversification. Chapter 3 then introduces fuzzy logic methodology and presents the model that is implemented to assess the non-farm income diversification potential in the survey countries. This is followed by a brief description of the database in Chapter 4. Simulation results are presented in Chapter 5 and Chapter 6. The last chapter summarises the main outcomes and gives policy recommendations.
urn:nbn:de:gbv:3:2-27254
Keywords: 330